Effectiveness of a Randomized Controlled Trial of Individual Reminiscence Therapy on Cognition, Mood and Quality of Life in Azorean Older Adults with Neurocognitive Disorders - Susana I. Justo-Henriques (MDPI AG, 2021)
Reminiscence therapy (RT) is a form of cognitive stimulation therapy that incorporates discussion of past activities, events, and experiences to stimulate individual memories; it has had some success in treating persons with neurocognitive disorders. This research aims to evaluate the ability of individual RT, using a simple reminiscence format, to improve the overall cognitive function, memory, executive functions, emotional status, and quality of life in older adults with neurocognitive disorders who received social care and support services. A multicenter randomized controlled trial was completed in the Azores archipelago (an independent region of Portugal) using repeated measures (pre-intervention, post-intervention, and follow-up). The intervention group underwent individual RT sessions, twice weekly for 13 weeks, while the control group completed regular activities administered as part of their program. Results did not reveal any significant differences between the intervention and control groups. While results did not reveal significant effects, a number of historical and contextual factors are considered as possible explanations for the lack of effects—namely, data collection occurring during the COVID-19 global pandemic, participant cohort effects, and therapist heterogeneity.